Chitons of the genus Cryptoplax (Mollusca: Polyplacophora) from the Spratly Islands, South China Sea - Sirenko, Boris I.; Saito, Hiroshi; Nguyen, Tai-Tu (Zootaxa, 2024)
Four species of the polyplacophoran genus Cryptoplax were identified among chiton samples collected from the Spratly Islands (Truong Sa), South China Sea. Among them, one is described as new species C. acerocostata n. sp.. The other three species, namely, C. larvaeformis (Burrow, 1815), C. brunoi Saito, 2023, and C. burrowi (E. A. Smith, 1884), are reported for the first time from the Spratly Islands. Color and SEM photographs of their features are given for all four species.